Social Media Network Analysis Corruption Harvey Moies on Twitter: Analisis Jaringan Media Sosial Korupsi Harvey Moies di Twitter - Amalia, Fara Putri; Abadi, Totok Wahyu (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Social Media Network Analysis is a way of mapping and describing network structures within social media conversations. However, the focus of this analysis is to find out the variety of netizen interactions that have emerged related to the Harvey Moies Corruption Case of Sandra Goddess's Husband on Twitter. This research uses qualitative methods. The topics considered in this study were social interactions on Twitter, from tweets, retweets, and comments. Each account has different characteristics and perspectives. The variety of conversations that have emerged tends to build public opinion and make the public suspect the legal handling of the case. The account's strength, especially in forming intense interaction, comes from the content posted from the account